Antioxidant Effect of Co-Treatment of Solanum aethiopicum and Ocimum gratissimum in Potassium Bromate-Induced Toxicity - Okon Victoria Edem; Enene Esu Ukpai (Darul Yasin Al Sys, 2026)
Potassium bromate induces oxidative cellular damage, creating a need to identify plant-derived interventions capable of strengthening endogenous antioxidant defenses. This study investigated the effects of combined Solanum aethiopicum and Ocimum gratissimum treatment on superoxide dismutase (SOD) and catalase (CAT) activities in potassium bromate-induced toxicity in Wistar rats. Thirty Wistar rats weighing 140–150 g were allocated into five groups of six animals each. Group 1 served as the normal control and received standard rat pellets and 0.2 mL of normal saline, whereas Group 2 received potassium bromate at 50 mg/kg. Groups 3 and 4 received potassium bromate followed by low-dose (150 mg/kg) and high-dose (300 mg/kg) co-treatment with S. aethiopicum and O. gratissimum, respectively, while Group 5 received potassium bromate followed by vitamin C at 100 mg/kg. Potassium bromate was administered to Groups 3–5 for two weeks before the respective treatments, which were administered daily for 14 days using an oropharyngeal cannula. SOD and CAT activities were assessed as oxidative stress biomarkers, and the resulting data were analyzed using analysis of variance. CAT activity increased significantly in the low-dose co-treatment group (p < .05), whereas the high-dose group showed a marginal but nonsignificant decrease relative to the control group (p > .05). The potassium bromate-only and potassium bromate plus vitamin C groups exhibited significantly reduced CAT activity compared with the control group (p < .05). Similarly, SOD activity showed a marginal significant increase in the low-dose co-treatment group but decreased significantly in the high-dose group relative to the control group (p < .05). Significant reductions in SOD activity were also observed in the potassium bromate-only and potassium bromate plus vitamin C groups (p < .05). These findings indicate that low-dose co-treatment with S. aethiopicum and O. gratissimum may enhance endogenous antioxidant enzyme activities and mitigate potassium bromate-induced cellular toxicity. However, the inconsistent response observed at the higher dose suggests a dose-dependent effect and highlights the importance of optimizing therapeutic dosage when evaluating these plants as potential antioxidant interventions.